Survey on the Development of Space-Integrated-Ground Information Network - Wei WU (天地一体化信息网络)
With the rapid development of ICT(information communication technology) and aerospace technology,the space network related technology is becoming mature,the global promotion of information technology fi eld has been fully expanded to all the space of human production,life and scientifi c research,including land,ocean,sky and space.For the China's information network,it is the focus to speed up the construction of the space-integrated-ground information network and realize the goal of seamless global coverage through the cooperation of the heaven and earth network.Firstly,the composition,network form and main characteristics of the space-ground integrated information network were described.Then,the development status and trend of the space-integrated-ground information networks at home and abroad were summarized.Finally,the key technologies needed to break through in the construction of the space- integrated-ground information network were analyzed,Hoping to provide reference for the development and construction of the space-integrated-ground information network.